Reflexivity, structure and agency: using reflexivity to understand Further Education students' Higher Education decision-making and choices. Issue 1 (2nd January 2019) - Baker, Zoe
Abstract: The purpose of this paper is to critically evaluate Archer's reflexive modalities in relation to Further Education (FE) students' higher education (HE) decision-making and choices. To do this, it draws on data from a qualitative, longitudinal narrative inquiry that explored how socioeconomically under-represented FE students made their HE decisions and choices. On a conceptual level, the research aimed to identify whether participants' HE decisions and choices were individualised or mediated by structure. Margaret Archer's reflexive modes were adapted to understand, first, how young people made their educational choices and decisions and, second, what role agency and structure played in this process. How participants' different reflexive modes were interpreted and how this facilitated more intricate understandings of how agency is exerted in the face of structural constraints are discussed. Yet, this paper also critically reflects on and questions the explanatory power of Archer's work in the context of this research.